Outcome Functions Yielding Walrasian and Lindahl Allocations at Nash Equilibrium Points - Hurwicz, L. (Review of Economic Studies, 1979)
Journal Article Outcome Functions Yielding Walrasian and Lindahl Allocations at Nash Equilibrium Points Get access L. Hurwicz L. Hurwicz University of Minnesota Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 46, Issue 2, April 1979, Pages 217–225, https://doi.org/10.2307/2297046 Published: 01 April 1979 Article history Received: 01 November 1976 Accepted: 01 December 1978 Published: 01 April 1979